Copy number variants and placental abnormalities in stillborn fetuses: A secondary analysis of the Stillbirth Collaborative Research Network study. (3rd August 2022) - Workalemahu, Tsegaselassie; Dalton, Susan; Allshouse, Amanda; Carey, Andrew Z.; Page, Jessica M.; Blue, Nathan R.; Thorsten, Vanessa; Goldenberg, Robert L.; Pinar, Halit; Reddy, Uma M.; Silver, Robert M.
Abstract: Objective: To examine the association of fetal/placental DNA copy number variants (CNVs) with pathologic placental lesions (PPLs) in pregnancies complicated by stillbirth. Design: A secondary analysis of stillbirth cases in the Stillbirth Collaborative Research Network case–control study. Setting: Multicenter, 59 hospitals in five geographical regions in the USA. Population: 387 stillbirth cases (2006–2008). Methods: Using standard definitions, PPLs were categorised by type including maternal vascular, fetal vascular, inflammatory and immune/idiopathic lesions. Single‐nucleotide polymorphism array detected CNVs of at least 500 kb. CNVs were classified into two groups: normal, defined as no CNV >500 kb or benign CNVs, and abnormal, defined as pathogenic or variants of unknown clinical significance. Main outcome measures: The proportions of abnormal CNVs and normal CNVs compared between stillbirth cases with and without PPLs using the Wald Chi‐square test. Results: Of 387 stillborn fetuses, 327 (84.5%) had maternal vascular PPLs and 60 (15.6%) had abnormal CNVs. Maternal vascular PPLs were more common in stillborn fetuses with abnormal CNVs than in those with normal CNVs (81.7% versus 64.2%; P = 0.008). The proportions of fetal vascular, maternal/fetal inflammatory and immune/idiopathic PPLs were similar among stillborn fetuses with abnormal CNVs and those with normal CNVs. Pathogenic CNVs in stillborn fetuses with maternal vascular PPLs spanned several known genes. Conclusions: Abnormal placental/fetal CNVs were associated with maternal vascular PPLs in stillbirth cases. The findings may provide insight into the mechanisms of specific genetic abnormalities associated with placental dysfunction and stillbirth.